2013
DOI: 10.1186/1471-2458-13-811
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cough etiquette maneuvers in disrupting the chain of transmission of infectious respiratory diseases

Abstract: BackgroundThe effectiveness of recommended measures, such as “cover your mouth when coughing”, in disrupting the chain of transmission of infectious respiratory diseases (IRD) has been questioned. The objective of the current study was to determine the effectiveness of simple primary respiratory hygiene/cough etiquette maneuvers in blocking droplets expelled as aerosol during coughing.MethodIn this study, 31 healthy non-smokers performed cough etiquette maneuvers in an effort to cover their voluntarily elicite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 9 publications
2
27
1
3
Order By: Relevance
“…32 However, it did not improve the practice of appropriately covering of the mouth when coughing, and a higher proportion of people reported the use of hands to cover their mouths instead of the more appropriate handkerchief/tissue or in the absence of that, the crook of the elbow post-versus pre-intervention. Although a recent observational cough etiquette study did not find these commonly publicized respiratory hygiene methods to satisfactorily block droplets that result in transmission of respiratory diseases, like TB, 33 they are still widely advocated by national and international health organizations 34,35 and may remain principal means of prevention of airborne diseases in poorer communities, like Idi Araba. Emphasis should, thus, be placed on encouraging these practices in future community intervention studies.…”
Section: Discussionmentioning
confidence: 99%
“…32 However, it did not improve the practice of appropriately covering of the mouth when coughing, and a higher proportion of people reported the use of hands to cover their mouths instead of the more appropriate handkerchief/tissue or in the absence of that, the crook of the elbow post-versus pre-intervention. Although a recent observational cough etiquette study did not find these commonly publicized respiratory hygiene methods to satisfactorily block droplets that result in transmission of respiratory diseases, like TB, 33 they are still widely advocated by national and international health organizations 34,35 and may remain principal means of prevention of airborne diseases in poorer communities, like Idi Araba. Emphasis should, thus, be placed on encouraging these practices in future community intervention studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other descriptions of this measure have included turning the head and covering the mouth when coughing and coughing or sneezing into a sleeve or elbow, rather than a hand. The rationale for not coughing into hands is to prevent subsequent contamination of other surfaces or objects (31). We conducted a search on November 6, 2018, and identified literature that was available in the databases during 1946-November 5, 2018.…”
Section: Respiratory Etiquettementioning
confidence: 99%
“…The authors did not specify the type of respiratory etiquette used by participants in the study. A laboratory-based study reported that common respiratory etiquette, including covering the mouth by hands, tissue, or sleeve/arm, was fairly ineffective in blocking the release and dispersion of droplets into the surrounding environment on the basis of measurement of emitted droplets with a laser diffraction system (31).…”
Section: Respiratory Etiquettementioning
confidence: 99%
“…Additionally, frequent education and oversight of HW, HH, and respiratory hygiene of nonmedical military personnel are required. The implementation of cough etiquette measures, such as "covering your mouth when coughing" (either with your arm or with a tissue), were not adequately shown to reduce the airborne spread of droplets leading to respiratory infection transmission in one experimental study (686); such measures have been promoted by health authorities in the United States (314) and in Europe (687) based on the judgment of public health professionals and have also been adopted by the U.S. military.…”
Section: Fomite-related Transmission Hand Washing and Hand Hygienementioning
confidence: 99%